Employee Turnover, Causes and Treatments: A Field Study at Dowaly Private Hospital (Entrepreneurship Journal for Finance and Business, 2024)
This study aims to serve the community by diagnosing a problem facing the Dowaly Private Hospital, represented by employee turnover. In this study, the problem of employee turnover was linked to human resources management practices, which include: estimating the need for human resources, job design, recruitment policies, training, development, performance appraisal, wages, incentives, and benefits. The study approach is an exploratory approach that relies on collecting as much information as possible to arrive at a diagnosis of the causes. The questionnaire was used as a tool for collecting data, in addition to personal interviews as a supporting tool for interpreting the results. The questionnaire was distributed to a random sample of (54) hospital employees. The statistical program (SPSS) was used to analyze the results. The research found that wages are the most common problem faced by working individuals, followed by estimating the need for human resources, incentives, benefits, job design, development, and performance appraisal, respectively. As for training and recruitment policies, they are at a high level at Dowaly Private Hospital. The study presented a set of recommendations that may reduce the problem of employee turnover that the Dowaly Private Hospital suffers from.